Purinergic signalling in autoimmunity: A role for the P2X7R in systemic lupus erythematosus? - Di Virgilio, Francesco (Biomed J, 2016)
Purinergic signalling plays a crucial role in immunity and autoimmunity. Among purinergic receptors, the P2X7 receptor (P2X7R) has an undisputed role as it is expressed to high level by immune cells, triggers cytokine release and modulates immune cell differentiation. In this review, we focus on evidence supporting a possible role of the P2X7R in the pathogenesis of systemic lupus erythematosus (SLE).